High incidence of pulmonary artery thrombosis after balloon pulmonary angioplasty in CTEPH patients receiving direct oral anticoagulants. (3rd October 2022) - Suetomi, T; Shimokawahara, H; Fukuda, Y; Kanezawa, M; Suruga, K; Hayashi, K; Miyagi, A; Kobashi, S; Sugiyama, Y; Shigetoshi, M; Tabuchi, I; Ogawa, A; et al.
Abstract: Background: Chronic thromboembolic pulmonary hypertension (CTEPH) requires life-long anticoagulant therapy, whereas limited data exist on the safety and efficacy of direct oral anticoagulants (DOACs) and vitamin K antagonists (VKAs) along with balloon pulmonary angioplasty (BPA). Objectives: To evaluate outcomes and complications in CTEPH following BPA for individuals receiving DOACs or VKAs. Methods: Consecutive CTEPH patients underwent BPA from September 2014 to August 2021 were included in a retrospective analysis. Complications during BPA, post-BPA hemodynamics and bleeding events were obtained from patient's medical records. Our routine follow-up "selective" pulmonary angiography, to evaluate all segmental pulmonary arteries one by one at six months and every year after final BPA session, was performed to elucidate the incidence of in-situ fresh floating thrombus. Results: Of total 250 individuals, 104 were treated with DOACs and 146 with VKAs following BPA. Mean observation period was 905 (SD ± 660) days. Total 1278 BPA sessions were performed among the period in which 409 sessions were treated with DOACs and 869 sessions with VKAs. Significant improvements in hemodynamics and functional status were observed in both groups following BPA. There was no significant difference of hemoptysis during BPA between DOACs and VKAs (7.1% vs 10.1%, P=0.131). Major bleeding events during observation period were equivalent in those treated with DOACs and VKAs. No significant re-elevation of pulmonary artery pressure was observed in both groups after BPA. Follow-up selective pulmonary angiography identified in-situ fresh floating thrombus in pulmonary artery in 22 cases of total 769 follow-up sessions. The occurrence of fresh thrombus was significantly higher in those receiving DOACs than VKAs in therapeutic range of PT-INR >1.8 (3.9% vs 1.2%, P=0.023) whereas no significant difference between DOACs and overall VKAs (3.9% vs 2.4%, P=0.177) Conclusions: Post-BPA hemodynamic outcomes and bleeding events appear unaffected by choice of anticoagulant. However, the incidence of in-situ pulmonary thrombosis detected by selective pulmonary angiography was significantly higher in those receiving DOACs than VKAs in therapeutic range, suggesting inadequate anticoagulation under current dose of DOACs. Our study provides a rationale for further examination to evaluate the efficacy of DOACs in CTEPH. Funding Acknowledgement: Type of funding sources: None.